A genome-wide association analysis of a broad psychosis phenotype identifies three loci for further investigation - Bramon, Elvira; Pirinen, Matti; Strange, Amy; Lin, Kuang; Freeman, Colin; Bellenguez, Céline; Su, Zhan; Band, Gavin; Pearson, Richard; Vukcevic, Damjan; Langford, Cordelia; Deloukas, Panos; et al. (Neuropsychopharmacology, 2014)
Bipolar disorder; genome-wide association; meta-analysis; polygenic score analysis; psychosis; schizophrenia.
Part of special issue: Schizophrenia: rare gene variants and uncommon syndromes